Rapid Remission With Upadacitinib in a Child With Refractory Crohn's Disease and ATM Mutation: A Case Report - Yan Liu, MD; XiaoMei Song, MD; LingYa Xiang, MD; Wei Tan, MD; Min Zou, MD; Hong Guo, MD (Current Therapeutic Research)
ABSTRACT: Managing pediatric Crohn's disease (PCD) presents challenges due to severe complications and higher biologic therapy needs. Transitioning from anti–tumor necrosis factor agents to off-label therapies adds complexity. Although upadacitinib has demonstrated efficacy and tolerability in adult inflammatory bowel disease and pediatric atopic dermatitis, there are limited data for its application in PCD. This case report delineates successful remission with upadacitinib in a child with CD refractory to infliximab, ustekinumab, adalimumab, thalidomide, and prednisone. Notably, the patient carried an ataxia telangiectasia mutated (ATM) gene mutation. These findings provide valuable evidence for PCD management and highlight the potential benefits of upadacitinib in this population.